A família Rubiaceae na Serra Geral de Licínio de Almeida - Borges, Rodrigo Lopes (2016)
In Brazil, Rubiaceae is the fourth family with greater diversity of species and is represented by 125 genera and 1392 species, mostly distributed in the Amazon and Atlantic forests. Due to the heterogeneity of habitat and vegetation types, Bahia stands out for the richness of species in the family (ca. 368 spp.) and by the record of many endemic species. Among the areas that are recognized by the lack of floristic inventories in the state, there is the southwest region, more precisely the areas that comprise the Espinhaço Septentrional. Thus, the aim of this study was to conduct a floristic and taxonomic survey of Rubiaceae to the Serra Geral of Licínio de Almeida (SGLA), Bahia. Ten field trips were conducted between July 2012 and May 2015, covering all existing vegetation types in the area. The collected materials were processed and deposited in the HUEFS and ALCB herbaria. Reference materials were also analyzed in visits to herbaria ALCB, CEPEC, HRB, HUEFS, RB and SPF. A number of 43 species distributed in 28 genera were recognized and collected, being Declieuxia (5 spp.), Borreria (3 spp.), Cordiera (3 spp.) and Psychotria (3 spp.) the most diverse genera. Following the previous floristic studies in Espinhaço Range, there are large number of genera (19) with only a single species. Psyllocarpus asparagoides, Psyllocarpus laricoides and Stachyarrhena reflexa are endemic to Minas Gerais and Bahia; Declieuxia passerina and Galianthe peruviana are new records for Bahia, and two species are considered new for science (Randia sp. and Staelia sp.). Keys to generic and specific identification, descriptions, taxonomic and biologic comments for all species are presented, as well as photos and illustrations.